COMPARISON OF PAIN INTENSITY BETWEEN LIDOCAINE GEL AND INTRAURETRAL TRAMADOL WITH LIDOCAINE GEL IN THE DJ STENT REMOVAL - Wijayanto, Cahyo; Doddy M. Soebadi; Djatisoesanto, Wahjoe (Indonesian Journal of Urology, 2021)
Objective: To determine the difference in pain intensity between the administration of a combination of tramadol and intraurethral lidocaine gel with only lidocaine gel during the removal of DJ stents. Material & Methods: This study was a prospective randomized clinical trial with 22 patients that were divided into 2 groups. Group 1 was given a combination of tramadol and lidocaine gel urethral injection 3 to 5 minutes before DJ stent removal, whereas group 2 was given lidocaine gel urethral injection 3-5 minutes before the removal. The inclusion criteria in this study was all patients with a DJ stent placement with 1 to 3 months prior to release who were willing to participate. The Wong-Baker scale was used directly to determine the scale of pain during the procedure. Mann Whitney analysis was used to analyze the findings. Results: Most patients in group 1 are shown to have a pain rating of 2. There are 2 patients with a high pain rating scale of 6 and 7. In group 2, most patients claimed that the procedure was painless. The average Wong-Baker pain scale in group 1 (2.9) compared to group 2 (0.36) was significantly different. Conclusion: The combination of intraurethral tramadol and 2% lidocaine gel can significantly decrease pain during DJ stent removal more effectively than sole intraurethral 2% lidocaine gel based on the Wong-Baker pain scale.